Phylogenetic analysis of strains of Ebola hemorrhagic fever virus - (:unkn) unknown (My University, 2007)
The virus Ebola, a negative non segmented RNA virus, is responsible for an hemorrhagic fever disease. Together with the Marburg virus, they compose the Filoviridae family (order Mononegavirales). Ebolavirus is geographically divided into 4 species : Zaire in Central Africa, Sudan in East Africa, Ivory Coast in West Africa, and Reston in Asia. Zaire ebolavirus, first appeared in 1976 in the Democratic Republic of Congo, has the highest mortality rate in humans (up to 88%) and has caused several outbreaks since its re-emergence in 1995. Outbreaks from 2001 to 2005 are characterized by multiple independent epidemic chains and large concomitant outbreaks in chimpanzee and gorillas. The viral glycoprotein (GP) gene was amplified and sequenced from samples obtained during the two last human outbreaks in 2003 and 2005 and samples from great apes carcasses found in the forest of the Gabon-Congo area since 2001. A second viral gene coding the nucleoprotein (NP) was amplified and sequenced from animal samples and human outbreaks since 2001. Phylogenetic analysis based on the GP gene showed the separation of Zaire ebolavirus strains into two genetic lineages. This separation is supported by molecular signatures specific to sequences of each lineage, and by genetic distances between sequences. Analysis based on the NP genes give the same results. However, the topology of human strains recovered between 2001 and 2003 is different in both trees. Results show the existence of two phylogenetic lineages and suggest a recombination event between strains of these lineages.The estimation of the age of the most recent common ancestor tracks back the separation of the lineages before the first appearance of Ebolavirus, up to 1975 (1971 estimated on the NP gene). With this method, the recombination event is dated to 1998-1999.
Keywords: African Research